2005
DOI: 10.1038/sj.cdd.4401804
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase-5 prevents neuronal apoptosis through ERK-mediated upregulation of Bcl-2

Abstract: Cyclin-dependent kinase-5 (Cdk5) is required for neuronal survival, but its targets in the apoptotic pathways remain unknown. Here, we show that Cdk5 kinase activity prevents neuronal apoptosis through the upregulation of Bcl-2. Treatment of SH-SY5Y cells with retinoid acid (RA) and brain-derived neurotrophic factor (BDNF) generates differentiated neuron-like cells. DNA damage triggers apoptosis in the undifferentiated cells through mitochondrial pathway; however, RA/BDNF treatment results in Bcl-2 upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 38 publications
1
66
0
Order By: Relevance
“…We have demonstrated that HOXA1-stimulated upregulation of Bcl-2 is mediated by p44/42 MAP kinase pathway. Previous studies have also demonstrated that Bcl-2 upregulation occurs through the p44/42 MAP kinase pathway, resulting in increased cell survival (Wang et al, 2005). Distinct from transcriptional upregulation of Bcl-2, p44/42 MAP kinase pathway also phosphorylates Bcl-2 at Ser-70.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that HOXA1-stimulated upregulation of Bcl-2 is mediated by p44/42 MAP kinase pathway. Previous studies have also demonstrated that Bcl-2 upregulation occurs through the p44/42 MAP kinase pathway, resulting in increased cell survival (Wang et al, 2005). Distinct from transcriptional upregulation of Bcl-2, p44/42 MAP kinase pathway also phosphorylates Bcl-2 at Ser-70.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mechanisms by which Cdk5 contributes to neuronal survival are largely unknown. Li et al, (Li et al, 2002) reported a key role for the kinase in promoting neuronal survival via negative regulation of the pro-apoptotic JNK3 pathway in UV-exposed neurons and a study by Wang et al, (Wang et al, 2006) suggested that basal Cdk5 activity is required to protect hippocampal neurons from serum deprivation via activation of Bcl-2. Conversely, other evidence suggests that abnormal Cdk5 activation is neurotoxic leading to apoptosis under both physiological and pathological conditions (Shelton and Johnson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cdk5 also promotes the survival of neurons by activating Akt through the well known neuregulin/phosphatidylinositol 3-kinase (PI3K) survival pathway, which leads to the down-regulation of proapoptotic factors (29). Cdk5 attenuates cell death either by up-regulating Bcl-2 through the phosphorylation of ERK (30) or by phosphorylating Bcl-2 to maintain its neuroprotective effect (31). However, whether Cdk5 acts as the anti-apoptotic factor in the PD model of neuronal cell death has not been determined.…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%